Features of the etiopathogenesis of lung lesions in tuberculosis - Mavlyanova, Umida Nematovna; Saidkulov, Doniyorjon Alisherovich (Science and Education, 2023)
Having a history of pulmonary tuberculosis (TB) is a risk factor for long-term respiratory failure. Post-tuberculous lung dysfunction often remains unrecognized, despite its relatively high prevalence and association with reduced quality of life. Importantly, the specific host and pathogen factors that cause lung injury remain unclear. The host immune response probably plays a major role in the lungs injury, as excessive inflammation and overexpression of lung matrix degrading proteases are common in tuberculosis. Variation in host genes that modulate these immune responses may determine the severity of lung injury, but this hypothesis remains largely untested.